Ramipril effects on cerebral blood flow and microcirculation in patients with essential arterial hypertension - L. I. Markova; A. E. Radzevich; I. V. Samsonova; E. V. Vasilyeva (Кардиоваскулярная терапия и профилактика)
Aim. To assess ramipril effects on microcirculation (MC) and cerebral blood flow (CBF) in patients with Stage II-III arterial hypertension (AH). Material and methods. In total, 37 patients with Stage II-III AH were examined. Thirty patients completed the study, receiving ramipril (2,5-20 mg/d) and hydrochlorothiazide (12,5 mg/d) for 6 months. At baseline, after one and six months, clinical examination, Doppler ultrasound of extracranial vessels, and MC assessment by conjunctival biomicroscopy were performed. Results. By the end of the study, target blood pressure level was achieved in 86% of the participants. Main parameters of MC and CBF correlated with each other. Ramipril therapy was associated with normalization of CBF and MC, primary due to the beneficial effects on capillary and intravascular MC. Conclusion. Inter-correlation between MC and CBF parameters support the interrelation between pathological processes in patients with AH and target organ damage, and also facilitate the assessment of ramipril protective effects on CBF. Long-term ramipril and hypothiazide therapy improved both MC and CBF in patients with Stage II-III AH.